Magnetic Resonance Imaging-Guided Laser Interstitial Thermal Therapy for Epilepsy: Systematic Review of Technique, Indications, and Outcomes. Issue 4 (24th January 2020) - Youngerman, Brett E; Save, Akshay V; McKhann, Guy M
Abstract: BACKGROUND: For patients with focal drug-resistant epilepsy (DRE), surgical resection of the epileptogenic zone (EZ) may offer seizure freedom and benefits for quality of life. Yet, concerns remain regarding invasiveness, morbidity, and neurocognitive side effects. Magnetic resonance-guided laser interstitial thermal therapy (MRgLITT) has emerged as a less invasive option for stereotactic ablation rather than resection of the EZ. OBJECTIVE: To provide an introduction to MRgLITT for epilepsy, including historical development, surgical technique, and role in therapy. METHODS: The development of MRgLITT is briefly recounted. A systematic review identified reported techniques and indication-specific outcomes of MRgLITT for DRE in human studies regardless of sample size or follow-up duration. Potential advantages and disadvantages compared to available alternatives for each indication are assessed in an unstructured review. RESULTS: Techniques and outcomes are reported for mesial temporal lobe epilepsy, hypothalamic hamartoma, focal cortical dysplasia, nonlesional epilepsy, tuberous sclerosis, periventricular nodular heterotopia, cerebral cavernous malformations, poststroke epilepsy, temporal encephalocele, and corpus callosotomy. CONCLUSION: MRgLITT offers access to foci virtually anywhere in the brain with minimal disruption of the overlying cortex and white matter, promising fewer neurological side effects and less surgical morbidity and pain. Compared to other ablative techniques, MRgLITT offers immediate, discrete lesions with real-time monitoring of temperature beyond the fiber tip for damage estimates and off-target injury prevention. Applications of MRgLITT for epilepsy are growing rapidly and, although more evidence of safety and efficacy is needed, there are potential advantages for some patients.